Art making and expressive art therapy in adult health and nursing care: A scoping review - Heli Vaartio-Rajalin; Regina Santamäki-Fischer; Pamela Jokisalo; Lisbeth Fagerström (Elsevier, 2021)
Objectives: While receptive art engagement is known to promote health and wellbeing, active art engagement has not been fully explored in health and nursing care. This review is to describe the existing knowledge on art making and expressive art therapy in adult health and nursing care between 2010 and 2020. Methods: Relevant studies and grey literature were searched and identified between March 17 and April 10, 2020 from EBSCO, CINAHL, Medline and ERIC databases and a general Internet search. Following data charting and extraction, the data (n = 42 papers) were summarized and reported in accordance with PRISMA-ScR guidelines. Results: In the included papers, both art making and expressive art therapy were seen in different health care and nursing contexts: yet not the home care context. The emphasis of art activities were group activities for chronically or terminally ill residents, adults aged 65 years or older. A focus on personal narrative was often seen, which may explain why art activities appear to be linked to acknowledging and building new strengths and skills, making meaning of experiences, personal growth, symptom alleviation, and communication; all used to foster collaboration between patients, patients' near-ones and health care professionals. Conclusions: Art activities appear to be suitable for every context and can promote personcenteredness and the measurement of nursing outcomes, and they should be considered an essential part of health and nursing care, nursing education and care for health care personnel.